What do we know about the diets of Aboriginal and Torres Strait Islander peoples in Australia? A systematic literature review - Sarah Whalan; Sara Farnbach; Lena Volk; Josephine Gwynn; Mark Lock; Kathy Trieu; Julie Brimblecombe; Jacqui Webster (Elsevier, 2017)
Abstract Objective: To provide an overview of published research on the dietary intake of Aboriginal and Torres Strait Islander peoples. Methods: Peer‐reviewed literature from 1990 to October 2016 was searched to identify studies that measured the dietary intake of Australian Aboriginal and Torres Strait Islander populations. Study quality was assessed using a purposely devised quality appraisal tool. Meta‐analysis was not possible due to the heterogeneity in dietary intake assessment methods. A narrative synthesis of study findings, where key themes were compared and contrasted was completed. Results: Twenty‐five articles from twenty studies with outcome measures related to dietary intake were included. Dietary intake was assessed by electronic store sales, store turnover method, 24‐hour dietary recall, food frequency questionnaire and short questions. Consistent findings were low reported intakes of fruit and vegetables and high intakes of total sugar and energy‐dense, nutrient‐poor food and beverages. Conclusions: While differences between studies and study quality limit the generalisability of the findings, most studies suggest that the diets of Aboriginal and Torres Strait Islander peoples are inadequate. Implications for public health: A more concerted approach to understanding dietary patterns of Aboriginal and Torres Strait Islander peoples is required to inform policy and practice to improve diet and nutrition.